2013
DOI: 10.1111/acer.12320
|View full text |Cite
|
Sign up to set email alerts
|

Little Evidence of a Role for the α1GABAA Subunit‐Containing Receptor in a Rhesus Monkey Model of Alcohol Drinking

Abstract: Background Alcohol potentiates GABAergic neurotransmission via action at the GABAA receptor. α1 subunit-containing GABAA receptors have been implicated as mediators, in part, of the behavioral and abuse-related effects of alcohol in rodents. Methods We systematically investigated the effects of one α1-preferring benzodiazepine agonist, zolpidem, and two antagonists, βCCT and 3-PBC, on oral self-administration of alcohol (2% w/v) or sucrose solution and observable behavior in rhesus macaques. We compared thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 47 publications
1
20
2
Order By: Relevance
“…Given the abuse liability of BZ and ethanol as individual reinforcers, it seems reasonable to assume that a major determinant of co-administration of these two drugs is related to their reinforcing effects. However, the equivocal findings of the aforementioned investigations of this topic (i.e., Barrett and Weinberg, 1975; Chan et al 1983a,b; Petry, 1995, 1997; Roehrs et al, 1984; Samson and Grant, 1985; Sawyer et al, 2014; Soderpalm and Hansen, 1998; Winger et al, 2007; current report) suggest that there may be little, if any, reliable enhancement of reinforcing effects when co-administering these drugs. One possibility is that BZ and ethanol co-administration is partially attributable to misuse of the medication, as opposed to recreational abuse.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Given the abuse liability of BZ and ethanol as individual reinforcers, it seems reasonable to assume that a major determinant of co-administration of these two drugs is related to their reinforcing effects. However, the equivocal findings of the aforementioned investigations of this topic (i.e., Barrett and Weinberg, 1975; Chan et al 1983a,b; Petry, 1995, 1997; Roehrs et al, 1984; Samson and Grant, 1985; Sawyer et al, 2014; Soderpalm and Hansen, 1998; Winger et al, 2007; current report) suggest that there may be little, if any, reliable enhancement of reinforcing effects when co-administering these drugs. One possibility is that BZ and ethanol co-administration is partially attributable to misuse of the medication, as opposed to recreational abuse.…”
Section: Discussioncontrasting
confidence: 73%
“…However, investigations of this possibility have yielded seemingly equivocal findings, at least in terms of ethanol consumption. For instance, studies have reported that BZ treatment increases (Petry, 1995; Petry, 1997; Sawyer et al, 2014; Schmitt et al, 2002; Soderpalm and Hansen, 1998; Winger et al, 2007), decreases (Chan et al, 1983a,b; Roehrs et al, 1984; Samson and Grant, 1985), or has no effect (Barrett and Weinberg, 1975; Leonard et al, 2006; Rimondini et al, 2002; Roehrs et al, 1984) on measures of ethanol consumption. However, the reinforcing effects of the BZ in isolation were only assessed in the study of Winger et al (2007), so the other reports were unable to compare the relative reinforcing effects of the mixture to that of each of its components (i.e., both the BZ and ethanol).…”
Section: Introductionmentioning
confidence: 99%
“…In baboons, 3-PBC reduced self-administration of alcohol but also had some effects on self-administration of a non-alcoholic reinforcer (Kaminski et al, 2013). In contrast to the findings in rodents and baboons, both 3-PBC and βCCT failed to attenuate alcohol drinking in rhesus macaques (Sawyer et al, 2014). The reason for this contradictory result is unclear; however, the highest dose of 3-PBC tested in Sawyer et al's study (10.0 mg/kg) was lower than that which reduced total g/kg alcohol intake in the baboon model (18.0 mg/kg).…”
Section: Discussioncontrasting
confidence: 99%
“…In primates, chronic administration of 3-PBC significantly decreased self-administration responses, volume consumed, and g/kg alcohol intake but also had some effects on self-administration of a non-alcoholic reinforcer in one study (Kaminski et al, 2013). In another study, chronic administration of 3-PBC and βCCT did not decrease alcohol intake or blood alcohol levels (Sawyer et al, 2014). …”
Section: Introductionmentioning
confidence: 98%
“…18, 24, 25 Behavioral studies in several species (e.g., rats, mice, primates) show that these ligands were BDZ antagonists, at the α1 Bz/GABA A subtype exhibiting competitive binding-site interactions with BDZ agonists over a broad range of doses. 18, 24, 26 In studies which involved the α1 subtype, they were shown to selectively reduce alcohol-motivated behaviors and more importantly, 3-PBC·HCl significantly reduced alcohol self-administration and reduced craving in baboons. 26 β-Carbolines 1·HCl and 3 displayed mixed weak agonist-antagonist profiles in vivo in alcohol preferring (P) and high alcohol drinking (HAD) rats.…”
Section: Introductionmentioning
confidence: 99%